Pemanfaatan Instagram Sebagai Media Promosi Perpustakaan Universitas Sari Mutiara Indonesia - Diana Maulida Zakiah; Fithria Rizka Sirait; Ernita Siagian (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2023)
The rapid development of technology, information and communication has given rise to various kinds of social media. These developments also had an impact on libraries. Libraries must be able to adapt to using various social media as a means of promotion, one of which is Instagram. This study aims to find out how Instagram is used as a promotional medium for the Library of Sari Mutiara Indonesia University by using several AIDA elements (Attention, Interest, Desire, Action). The research method used is descriptive qualitative, using interview techniques with 7 informants. The results showed that the use of the Instagram social media application was considered quite effective as a media promotion for the library, this is because the Instagram application can reach a wide audience, the library is also good at displaying content on Instagram using the same theme for several uploads, but it is necessary consistency of the library to continue and schedule the time to post content